The main measures adopted for vector and parasitological control of malaria: A systematic review (International Seven Journal of Health Research, 2023)
Malaria is a parasitic disease caused by protozoa of the genus Plasmodium, which for many years have created serious public health problems worldwide, being one of the main causes of morbidity and mortality in children under 5 years of age and pregnant women. One of the most common forms of transmission is through the bite of an infected female Anopheles mosquito. Due to the lack of an effective vaccine so far, several interventionist measures are carried out to combat it through insecticides against insect vectors. To this end, mosquito nets treated with insecticides based on pyrethroids or deltamethrin have been developed over the years, which facilitated the reduction of malaria transmission in many countries that used them. In addition, there is Causal Chemoprophylaxis (QC), which the World Health Organization (WHO) recommends for use preferably for people classified in the risk group due to the adverse effects that these drugs cause in the victim. This work aims to carry out a survey of the scientific evidence on the main strategies that are adopted for the control of the vector and the malaria parasite, in the period between 2012 and 2020. In this logic, a search was carried out for scientific articles, whose approach was related to the intervention actions used to control the malaria vector and parasite. In this way, a search was made for scientific articles available exclusively in the Scielo journal database, where the articles were filtered, strictly taking advantage of those published in the period from 2012 to 2020. As controlled descriptors, the terms and expressions “control”, “Malaria”, with the Boolean interposition “AND”. 35 articles were obtained, of which 16 were excluded for not addressing the subject of intervention actions for malaria control. Of the 19 selected studies, 12 specifically reported malaria vector or parasite control strategies while 7 dealt only with action plans used for malaria epidemiological surveillance. It is recommended that the next research to be carried out, research more about natural products of plant origin considered promising for a possible replacement of such antibiotics.